Al-Qur'an Communication on Hedonism Lifestyle Problems Through the Construction of the Meaning of Love in QS. Ali Imran/3:14 - Ruslan Sangaji; Eka Nurfikra (State Islamic Institute of Bone, Indonesia, 2023)
The tendency to love something as human nature is often misunderstood and not understood by humans as it is in QS. Ali Imran/3:14. This paper will answer how Allah communicates QS. Ali Imran/3:14 and its relation to the problems of love which give birth to a hedonic lifestyle. This research is a research library research. All data is sourced from library data using scientific interpretation analysis. The results of the study show that Allah SWT has bestowed love on humans for some of the objects listed in QS. Ä€li 'ImrÄn/3:14, includes love for spouses, offspring, and various forms of property. Crimes resulting from desecration of love like that are included in the category of global problems which are one of the obstacles in realizing the Sustainable Development Goals (SDGs) which are designed to bring about the welfare of the world community. Solutions to this global problem can be found through religious communication based on the Qur'an and supported by awareness of scientific findings. Through a healthy lifestyle that is supported by spiritual fulfillment through worship, it will produce continuously controlled hormone levels.